Techno-rational knowing and phronesis: the professional practice of one middle-distance running coach - Barker-Ruchti, N.; Barker, D.; Annerstedt, C. (Reflective Practice. International and Multidisciplinary Perspectives, 2014)
Sport coaching has traditionally been seen as a techno-rational activity. In recent years, there has been a `subjective turn`. Intuitive, as well as situation-specific interpretations are today perceived as necessary to handle complex, dynamic and often unpredictable sport environments. While a considerable body of research has attempted to understand coaching practice, research on intuitive and situation-dependent praxis is only emerging. Phronesis ? mostly defined as practical wisdom or practical rationality ? has been put forward as a useful theoretical concept to frame such coaching practice. In this contribution, we employ phronesis as part of sustainability science to consider the coaching of one top-level middle-distance running coach. Observations, informal talks and semi-structured interviews produced the empirical materials for this analysis. The results suggest that the coach`s practice was guided by both techno-rational and phronetic knowledge. While techno-rational knowledge manifested itself in a focus on time and control, the latter was reflected in a concern for impact, focus on community, authenticity and modesty. From a phronetic perspective, these characteristics can be seen as morally just and important precursors for sustainable sport.